Interactive e-modules based on local wisdom in learning the Indonesian language and literature as an implementation of the independent curriculum in elementary schools throughout Jember Regency - Nurdianasari, Nindya; Suhartiningsih , Suhartiningsih; Proborini, Chandra Ayu; Ratri, Luri Santika (Universitas Ahmad Dahlan, 2023)
The product produced in this study is an interactive e-module based on Jember local wisdom in learning the Indonesian Language and Literature as an implementation of the Merdeka Curriculum. During the even semester of the academic year 2022-2023, this study was conducted at SDN Panti 01, SDN Ajung 01, and SDN Bagorejo 03. Research and Development is the term used by Borg and Gall. The purpose of this study is to produce, validate, and test interactive e-module products based on Jember Local wisdom in learning the Indonesian Language and Literature as an implementation of the Merdeka Curriculum. In this study, questionnaires and documentation were used to collect data. The local wisdom developed in the E-Module is (1) Edamame; (2) Okras; (3) Scar war; (4) Tiger Cadduk Cans; (5) Patrols; (6) JFC; (7) Samper Sarong Dance; and (8) Lahbako Dance; (9) Papuma Beach; and (10) Jember Mini Zoo. Considering the validation outcomes, the interactive e-module based on Jembers local wisdom is included in the decent category with a score of 76.8. Because it fell between the range of 71.00 and 80.99 scores, the calculation of student replies yielded a value of 80.33%, which was included in the practical category.